Towards a sustainable development strategy Fisheries sector in Arab Republic of Egypt (A proposed economic study) - El- Safty, Mohamed Fawzy; Mostafa, Doaa Ahmed Awad (Iraqi Journal of Aquaculture, 2021)
The amount of annual change in the total quantity of Egyptian fish production from various sources about 11.45 tons, with an annual growth rate of approximately 1.1% of the annual average of about 1000.9 tons during the study period (2001-2015). The amount of annual change in the volume of consumption of fish in Egypt during the same study period of about 0.65 tons, with an annual growth rate of approximately 0.1% of the annual average of about 1185.4 thousand tons. The amount of annual change in the average per capita consumption of fish in Egypt during the same study period of about 0.02 kg/year, with an annual growth rate of about 0.12% of the annual average of about 16.3 kg/year. The amount of annual change in the self-sufficiency rate of fish in Egypt during the study period of about 0.55% with an annual growth rate of about 0.7% of the annual average of about 84.5%. The amount of annual change in the volume of exports of fish in Egypt during the study period of about 0.01 tons, with an annual growth rate of approximately 0.2% of the annual average of about 5.2 tons. The amount of annual change in the evolution of the volume of imports of fish in Egypt during the study period of about 0.45 tons, with an annual growth rate of about 0.24% of the annual average of about 189.5 million tonnes